Development of Cell Volume Regulatory Mechanisms During Oocyte Growth and Meiotic Maturation - Richard, Samantha (Université d'Ottawa / University of Ottawa, 2017)
The ability of oocytes and early cleavage-stage embryos to regulate their volume is essential to avoid developmental arrests at in vivo-osmolarities. This is accomplished primarily via GLYT1-mediated glycine transport into the cells. GLYT1 activity has previously been shown to be absent in freshly isolated oocytes but becomes activated ~3-4 hours after oocyte maturation has been initiated either by isolation from ovarian follicles in vitro or following an ovulatory stimulus in vivo. GLYT1 activity then persists until the 4-cell stage of preimplantation embryo development. GLYT1 has been shown to spontaneously activate in oocytes that are isolated from follicles either as denuded oocytes or as cumulus-oocyte complexes (COCs), this implies that GLYT1 activity is suppressed in intact follicles in the ovary. However, it is not known how GLYT1 activity is suppressed within the ovarian follicle or how initial GLYT1 activation occurs. The activation of independent cell volume regulation in oocytes first involves the release of the strong adhesion between the oocyte and zona pellucida (ZP) followed by secondary GLYT1 activation. These two processes have been shown to occur spontaneously in fully grown oocytes following isolation from ovarian follicles, however, it is not known whether small growing oocytes within ovarian follicles already possess the ability to detach from the ZP and activate GLYT1. An osmotic assay was used to determine when during oogenesis oocytes are first able to detach from the ZP while the ability to activate GLYT1 was determined by measuring [3H]-glycine uptake into oocytes. I found that oocytes acquire the ability to detach from the ZP when they are nearly fully grown and similarly, that high levels of GLYT1 activity first develop in isolated oocytes during the late stages of oogenesis. Furthermore, I showed that SLC6A9 protein (GLYT1 transporter protein) and Slc6a9a transcripts steadily increased during oogenesis with SLC6A9 protein becoming localized to the oocyte plasma membrane during oocyte growth with predominant membrane localization apparent in fully grown oocytes. Taken together, these results suggest that oocytes become able to detach from the ZP and fully activate GLYT1 towards the end of oogenesis but that these processes remain suppressed in the ovarian follicle. Intact and punctured antral follicles were used as a model to examine the potential mechanism(s) mediating GLYT1 suppression before ovulation is triggered. Using these models, I found that GLYT1 activity remains suppressed within preovulatory antral follicles in contrast to the spontaneous GLYT1 activation that occurred in isolated denuded oocytes or within COCs. Recently, the mechanism mediating oocyte maintenance of prophase I arrest within the ovarian follicle was elucidated and was shown to depend on the release of Natriuretic Peptide Precursor C (NPPC) from mural granulosa cells (MGCs) into follicular fluid which binds to NPR2 guanylate cyclases on cumulus cells stimulating the production of cyclic GMP (cGMP) within these cells. Diffusion of cGMP from cumulus granulosa cells to the oocyte via gap junctions is required to maintain meiotic arrest. Although GLYT1 activation and meiotic resumption are both suppressed in antral follicles prior to the ovulatory trigger and these two processes occur simultaneously following oocyte isolation from ovaries, I have shown here that GLYT1 suppression within the preovulatory antral follicle is mediated by a mechanism distinct from the gap junction-dependent NPPC-cGMP pathway controlling meiotic arrest. I also showed for the first time a direct requirement for meiotic arrest of both gap junctions between granulosa cells (composed of connexin-43) and between the inner layer of cumulus granulosa cells and the oocyte (composed of connexin-37). Since I showed that GLYT1 was suppressed in isolated antral follicles but not COCs, I hypothesized that MGCs are required to maintain low GLYT1 activity in antral follicles. I showed here that MGCs isolated from preovulatory antral follicles were sufficient to maintain GLYT1 suppression in co-cultured COCs, but not denuded oocytes. Furthermore, I found that GLYT1 activity was suppressed in COCs cultured in conditioned medium from MGC cultures. Thus, GLYT1 activity appears to be suppressed within the ovary prior to the ovulatory LH-stimulus likely by an unidentified inhibitory signal within the ovarian follicle originating from the MGCs and propagated by a gap junction-independent mechanism involving multiple cell types in the follicle.
Keywords: GLYT1; Oocyte; Volume Regulation; Meiotic Maturation